The influence of Trust, Switching Cost and Emotional Commitment on Bank Mandiri and Bank BNI 46 - Haryo Bagus Novrianto (Business and Entrepreneurial Review, 2007)
The background of this research was across product and services, the stiff competition force companies in adopting relationship marketing as competitive and growth srategy. Service industry has become an industry of fierce and intense competitions. The objectives of this research were to identify the effect of trust, switching cost, and emotional commitment on word of mouth and cooperation. The design of this research applies hypothesis testing to examine all hypotheses in this study. The methods used in this study were multiple regressions between independent variables and dependent variable. Data analysis used in this research was collected by distributing questionnaires which were distributed to 110 respondents in Jakarta. Therewere 105 responses of which 100 were completed and usable for analyzed by multiple regressions. The result of this research concluded that; first, trust has positive and significant impact on emmotional commitment. Second, trust and emotional commitment have positive word of mouth and cooperation. Third, switching cost has not significant and positive impact on positive word of mouth and cooperation.